2012
DOI: 10.1007/s12070-012-0548-z
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness of Pediatric Cholesteatoma. Do We Have an Evidence?

Abstract: To compare pediatric and adult patients, affected by cholesteatoma for the clinical presentation, disease extent and final outcome. This is a prospective study in which 60 cases of unsafe chronic suppurative otitis media with cholesteatoma were included. These cases were divided into two groups of 30 cases each on the basis of age. All patients were subjected to detailed clinical examination. A high resolution computed tomography of the temporal bone was done in all the cases. An innovative grading system was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…We found significant differences between childhood cholesteatoma and adult disease, the former of which was more extensive and destructive at the time of surgery. These results support the findings of other studies that have suggested cholesteatoma in children to be more aggressive 16 , 20 , 21 . Although many studies have reviewed children and adult populations with cholesteatoma, a limited number of studies have directly compared these two groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found significant differences between childhood cholesteatoma and adult disease, the former of which was more extensive and destructive at the time of surgery. These results support the findings of other studies that have suggested cholesteatoma in children to be more aggressive 16 , 20 , 21 . Although many studies have reviewed children and adult populations with cholesteatoma, a limited number of studies have directly compared these two groups.…”
Section: Discussionsupporting
confidence: 89%
“…found increased neuro-otological symptoms in adults compared to children 14 . Regarding complications, while some authors have reported fewer complications in children, 15 others have not found any statistical differences between the two groups 16 . Mallet et al .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is essential to clarify that the operation technique is not the only factor influencing the risk of cholesteatoma recidivism. In addition, this risk is affected by the extent of the disease (especially mastoid extension), ossicular chain disruption, cholesteatoma location and preoperative ear discharge . However, it should be emphasized that all studies investigating the aforementioned risk factors included only children or studied a population consisting of both children and adults .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cholesteatoma is known to be more aggressive than cholesteatoma acquired later in age [1]. The incidence of recidivist disease in pediatric cholesteatoma is much higher than in adult patients [2]. Moreover, the incidence of cholesteatoma in children with cleft palate is reported higher (1.8-9.2%) than those without (0.3-0.6%) [3,4].…”
Section: Introductionmentioning
confidence: 98%